Azerbaijan’s Policy Regarding Misappropriation of Armenian Cultural Heritage in the Light of International Principles (Authenticity, Integrity, Cultural Significance, Outstanding Universal Value) of Heritage Protection - Tigranyan, Armine (History and Culture, 2022)
The aggressive policy of Azerbaijan towards the cultural heritage of Artsakh is not limited to destruction, demolition and physical violence against the Armenian heritage. A much more dangerous policy exists and is widely used, which, while outwardly preserving the main structure of the heritage, alienates from it the most important thing - the Armenian identity. Alienation of identity occurs through change, appropriation, Azerbaijanization, Turkification and other ways. This policy is a gross violation of the basic international principles for the protection of cultural heritage: the principles of “authenticity”, “cultural significance”, “integrity” and “exclusivity”. This way of working is also a significant obstacle to the comprehensive preservation of heritage elements, vitality, principles of naturalness and cultural habitat. By distorting historical facts, Azerbaijan neutralizes the true tradition of heritage, violates the possibility of transferring value to generations with its main function, its integrity, details, elements and attributes. The attribution of Armenian values ​​to Caucasian Albanians, Turks or their Azerbaijaization takes away these values ​​from their real owners, the Armenian community of Artsakh, according to whose life experience, knowledge and skills they were created and must be preserved as such. According to the international principles of heritage, its idea, the feelings it evokes, the potential of the heritage, the information it carries, can often be more than the structure itself, but Azerbaijan consistently manipulates them. The appropriated Armenian heritage is the embodiment of the creative genius of the Artsakh Armenian community and its preservation is entrusted to the Artsakh Armenian community itself, but it is purposefully constantly alienated from its native people and the whole world.
Keywords: protection of cultural heritage; international principles of heritage; authenticity; integrity; cultural significance; exclusivity (outstanding universal value); misappropriation of Armenian heritage; alteration of the function of heritage; vandalism of Azerbaijan